Presidential Discretion and Ministerial Inflation: A Normative Critique of the Amendment to Indonesia’s State Ministry Law - Akbar, Muhammad Jihadil; Uyun, Dhia Al; Prasetyo, Ngesti Dwi (Institut Agama Islam Negeri Ponorogo, 2025)
The amendment to Article 15 of the State Ministry Law, which eliminated the cap on ministries and replaced it with